Banana‐shaped electron acceptors with an electron‐rich core fragment and 3D packing capability. Issue 1 (21st June 2022) - Li, Pengqi; Meng, Xianyi; Jin, Ke; Xu, Zhiwei; Zhang, Jianqi; Zhang, Lixiu; Niu, Chuang; Tan, Furui; Yi, Chenyi; Xiao, Zuo; Feng, Yaqing; Wang, Guan‐Wu; et al.
Abstract: The emergence of Y6‐type nonfullerene acceptors has greatly enhanced the power conversion efficiency (PCE) of organic solar cells (OSCs). However, which structural feature is responsible for the excellent photovoltaic performance is still under debate. In this study, two Y6‐like acceptors BDOTP‐1 and BDOTP‐2 were designed. Different from previous Y6‐type acceptors featuring an A–D–Aʹ–D–A structure, BDOTP‐1, and BDOTP‐2 have no electron‐deficient Aʹ fragment in the core unit. Instead, there is an electron‐rich dibenzodioxine fragment in the core. Although this modification leads to a marked change in the molecular dipole moment, electrostatic potential, frontier orbitals, and energy levels, BDOTP acceptors retain similar three‐dimensional packing capability as Y6‐type acceptors due to the similar banana‐shaped molecular configuration. BDOTP acceptors show good performance in OSCs. High PCEs of up to 18.51% (certified 17.9%) are achieved. This study suggests that the banana‐shaped configuration instead of the A–D–Aʹ–D–A structure is likely to be the determining factor in realizing high photovoltaic performance. Abstract : Acceptors BDOTP‐1 and BDOTP‐2 with an electron‐rich core fragment and three‐dimensional packing capability are developed. The excellent photovoltaic performance of Y6‐type acceptors might mainly be attributed to the banana‐shaped molecular configuration instead of the A–D–Aʹ–D–A structure.